Becoming more integrated into the community: a qualitative study of learners’ experiences of the learning environment in a longitudinal integrated clerkship - Kelly, Martina; Perez, Grace; Ram, Rithesh; Begert, Nicolle; Keshvara, Anil; Johnston, Aaron (Frontiers in Medicine, 2025)
BackgroundWhile the significance of continuity in the learning environment of longitudinal integrated clerkships (LIC) is widely acknowledged, most studies have focused on continuity of the learner-preceptor relationship and learner-patient relationship. Yet learning environments contain a myriad of wider social dimensions, such as personal relationships, interactions with members of the multidisciplinary team and the broader social context of rural communities; learning is situated within a broad social system. This study aimed to understand how learners experience learning during a LIC.MethodsQualitative interviews involving learners in a final year LIC in Western Canada were analyzed inductively, informed by Bronfenbrenner’s ecological systems theory and team reflexivity.ResultsOf the LIC cohort of 22, 18 consented to be interviewed. The participants were mature, had previous careers and most had families with them. Beyond the continuity of relationships with preceptors and patients, the study uncovered other factors that influenced the learning of the LIC students. Apart from students’ interactions in the clinical settings (patients, preceptors and other multi-disciplinary teams), factors such as personal relationships, community connections, learning in a resource-strained environment, geographical isolation, and other socio-political dynamics, impacted the LIC learner experiences of continuity and community integration. The results showed that LIC students were self-directed in their learning and the LIC experience shaped their professional development and facilitated their readiness for future residency.ConclusionThe relationship between learner and primary preceptor is central but the overall experience of the learning environment is much broader and more complex. Much of the richness of the LIC experience is embedded in the complexity of the learning environment. The use of Bronfenbrenner’s ecological systems theory as a framework for understanding the complexity of the learning environment will be of interest to LIC leaders. The authors recommend potential action points at multiple system levels for medical schools to support the experiences of continuity and integration in the LIC environment and enhance students’ professional journey. These will also provide supports for the ongoing active advocacy work regarding achieving a sustainable rural health workforce now and into the future.